DASAPUSHPAM: THE TRADITIONAL USES AND THE THERAPEUTIC POTENTIAL OF TEN SACRED PLANTS OF KERALA STATE IN INDIA - K. Jiny Varghese; J. Anila; R. Nagalekshmi; S. Resiya and J. Sonu (International Journal of Pharmaceutical Sciences and Research, 2010)
The Western Ghats of Kerala is famous for its medicinal plant wealth and the tradition of indigenous system of therapy, specifically the Ayurveda. Dasapushpam constitute a group of ten potential herbs which are culturally and medicinally significant to the people of Kerala in India. They are a group of ten herbs with which the ladies decorate their hairs and dance the Thiruvathira Kali on the day of Thiruvathira in the Malayalam month of Dhanu. These plants are therapeutically very active for various diseases and ailments. Many of them are traditionally used from time immemorial. Some of them are scientifically validated for various bioactivities. Still there are lots of possibilities for potential pharmacological activities from these herbs, yet to be explored. This article would give an insight of these ten sacred plants and their properties to further popularise these plants.